SOCIAL TYPES CHARACTERISTIC OF THE CHACO TERRITORIANO (1884-1950). THEIR CONDITIONS OF LIFE, AND INFLUENCE ON THE IDENTITY OF THIS SPACE. - Mari, Oscar Ernesto (Revista de Historia Social y de las Mentalidades, 2013)
The occupation of the Southern Chaco Argentine  between ends of the nineteenth century  and early decades of the 20th, was boosted  by successive phases colonizers that they  accompanied differentiated economics cycles. In  each one of these moments, that were given in  different geographic areas within the Territory,  went forming social groups individuals that  contributed the first identity traits to this society  in training. Within these, emerged social types  that motivated first images with that the domestic  society identified to Chaco. Living conditions  and work, and it contributes the cultural of some  sectors representing the rural field of Chaco in  this period, are issues addressed in the current  article.
Keywords: Chaco; Territory; Identity; Rural Social Types